PENGARUH LATIHAN SMALL SIDE GAMES TERHADAP KEMAMPUAN DRIBBLING BOLA SISWA DALAM PERMAINAN SEPAKBOLA - Sabri Sabri (Jurnal keilmuan dan Kependidikan dasar, 2023)
ABSTRACT This research is motivated by various problems that occur in students 'soccer games, including the frequent loose balls in their control, the students' ability to process low movements such as agility, flexibility, balance, speed and others. This study aims to see the effect of Small Sided Games Training on Dribbling Ability in Football Games in elementary school students who take extracurricular soccer training. The design of this study was the experimental randomized control group pretest-posttest design. The population consisted of 20 elementary school students in Sukamaju 2, Labuan sub-district. Pupolation was divided into two groups randomly, where the experimental group was given small side game exercises while the control group continued to do exercises using conventional methods. Each group received a test before and after treatment. This research was conducted using t-test analysis with analysis using the SPSS statistical program. This hypothesis testing was conducted to determine the effect of small sided games training on dribbling skills in soccer games among students at SD Negeri Sukamaju 2, Labuan District, Pandeglang Regency. Based on the results of the analysis evidenced by the calculated significance value in the t test of the pretest and posttest groups, the result was 11,895 with sig. 0.000 is smaller than 0.05 (sig <0.05), therefore it can be stated that small side game practice can improve students' ball dribbling skills in playing soccer well. Keywords: Football, small side game, ball dribbling